The potency of Berastagi sweet orange (Citrus sinensis) peel extract for obesity treatment: An experimental study in male rats - WINDA RIZKI PEBRINA BATUBARA; TRI NUGRAHA SUSILAWATI; DONO INDARTO (Nusantara Bioscience, 2023)
Abstract. Batubara WRP, Susilawati TN, Indarto D. 2023. The potency of Berastagi sweet orange (Citrus sinensis) peel extract for obesity treatment: A study in the rats. Nusantara Bioscience 15: 251-257. Obesity is an abnormal accumulation of body fat and is a trigger factor for various degenerative diseases. Obese continues to grow every year in the world. This study aimed to investigate the effects of Orange Peel Extract (OPE) on Body Weight (BW), obesity index (Lee Index), Body Fat Percentage (BFP) and visceral fat in obese-model rats. Thirty male Wistar rats were divided into 5 groups: controls (negative/NC given aquadest and positive/PC given orlistat 12.3 mg/kgBW/day) and interventions (OPE 1-3) given OPE 250, 500 and 750 mg/kgBW/day, respectively. All rats were fed a high-fat, high-fructose (HFHFr) diet for 28 days. Statistical analysis was performed using ANOVA and Friedman test with p<0.05. The average BW in all groups increased significantly after 14 and 28 days of the intervention (p=0.005). A significant decrease in the obesity index average was found in the OPE 2 and 3 groups (p=0.028 and p=0.034) compared to the NC group. The OPE 1-3 and PC group significantly decreased in average BFP compared with the NC group on the 28th day of intervention (p<0.05). In conclusion, OPE can reduce obesity induced by HFHFr. Future research could be directed to evaluate the OPE side effects for obesity treatment.